Synthesis, characterization, controlled release and cytotoxic effect of anthranilic acid-loaded chitosan and polyethylene glycol-magnetic nanoparticles on murine macrophage raw 264.7 cells - Al Ali, Samer Hasan Hussein; Arulselvan, Palanisamy; Hussein, Mohd. Zobir; Fakurazi, Sharida; Ismail, Maznah; Dorniani, Dena; El Zowalaty, Mohammad Ezzat (World Scientific Publishing, 2014)
Magnetic nanoparticles (MNPs) were prepared by the coprecipitation method using a molar ratio of Fe3+:Fe2+ of 2:1. The surface of MNP was coated with chitosan (CS) and polyethylene glycol (PEG) to form CS–MNP and PEG–MNP nanoparticles, respectively. Anthranilic acid (AA) was loaded on the surface of the resulting nanoparticles to form AA–CS–MNP and AA–PEG–MNP nanocomposites, respectively. The nanocomposites obtained were characterized using powder X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), thermogravimetry analysis (TGA), vibrating sample magnetometer (VSM) and scanning electron microscopy (SEM). XRD results showed that the as-synthesized nanocomposites are pure magnetite. FTIR results analysis indicated the existence of two polymers on the particle surface of the MNP and the presence of loaded AA on the surface of CS–MNP and PEG–MNP nanoparticles. Anthranilic acid loading and the release profiles of AA–CS–MNP and AA–PEG–MNP nanocomposites showed that up to 8.8% and 5.5% of the adsorbed drug were released in 670 min and 771 min, respectively. Anthranilic acid release profiles followed a pseudo-second-order kinetic controlled process. The cytotoxicity of the as-synthesized anthranilic acid nanocomposities were determined using MTT assay using murine macrophage RAW 264.7 cells. MTT results showed that the cytotoxic effects of AA–CS–MNP were higher than AA–PEG–MNP against the tested cells as compared to free anthranilic acid. In this manner, this study introduces novel anthranilic acid nanocomposites that can be used on-demand for biomedical applications.